Implications of regulating commodity derivatives markets in the USA and EU - Ghosh, Jayati (PSL Quarterly Review, 2011)
The argument for effective financial regulation to curb financial activity and associated volatility in primary commodity markets is now more compelling than ever, in the context of the renewed increase in food prices. However, as in much other financial regulation, the devil is in the detail. This paper considers recent patterns in global food markets and discusses some of the implications of recent moves to regulate financial activity in commodity futures markets in the US and the EU. Specific regulatory issues are considered and alternative strategies are considered. JEL Codes: F02, F14, G18, N50